The Evolutionary Fate of the Horizontally Transferred Agrobacterial Mikimopine Synthase Gene in the Genera Nicotiana and Linaria - Kovacova, Viera; Zluvova, Jitka; Janousek, Bohuslav; Talianova, Martina; Vyskot, Boris (PLOS ONE, 2014)
Few cases of spontaneously horizontally transferred bacterial genes into plant genomes have been described to date. The occurrence of horizontally transferred genes from the T-DNA of Agrobacterium rhizogenes into the plant genome has been reported in the genus Nicotiana and in the species Linaria vulgaris. Here we compare patterns of evolution in one of these genes (a gene encoding mikimopine synthase, mis) following three different events of horizontal gene transfer (HGT). As this gene plays an important role in Agrobacterium, and there are known cases showing that genes from pathogens can acquire plant protection function, we hypothesised that in at least some of the studied species we will find signs of selective pressures influencing mis sequence. The mikimopine synthase (mis) gene evolved in a different manner in the branch leading to Nicotiana tabacum and N. tomentosiformis, in the branch leading to N. glauca and in the genus Linaria. Our analyses of the genus Linaria suggest that the mis gene began to degenerate soon after the HGT. In contrast, in the case of N. glauca, the mis gene evolved under significant selective pressures. This suggests a possible role of mikimopine synthase in current N. glauca and its ancestor(s). In N. tabacum and N. tomentosiformis, the mis gene has a common frameshift mutation that disrupted its open reading frame. Interestingly, our results suggest that in spite of the frameshift, the mis gene could evolve under selective pressures. This sequence may still have some regulatory role at the RNA level as suggested by coverage of this sequence by small RNAs in N. tabacum.